URGENSI KEBIJAKAN KRIMINALISASI PENELANTARAN IZIN USAHA PERTAMBANGAN BATUBARA OLEH KORPORASI - Simangunsong, Gusfen Alextron; Utama, Yos Johan; Rozah, Umi (Faculty of Law, Universitas Pasundan, 2024)
Development in the mining sector is an integral part of national development which aims to support industrialization programs to provide domestic raw materials and increase state revenues from foreign exchange and open up the widest possible employment opportunities in order to improve welfare. The implementation of mining business activities must begin with the ownership of a Mining Business License granted to business entities, cooperatives and individuals. The conditions that occur in reality record that there are not a few cases of illegal mining that cost the State around 38 trillion per year. It was recorded in 2021 that there were 2,741 unlicensed mining locations spread across 29 provinces in Indonesia. Of these points, there are 2,645 mineral and coal commodities and 96 coal commodity locations. Given the importance of the mining sector, the government positions the mining sector as the livelihood of many people. As mandated by the Constitution Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Law enforcement of the obligations of Coal Mining Business License holders has not been effective, seen from the five factors that have been fulfilled, namely the legal factors themselves, facility factors, law enforcement factors, legal awareness factors, and legal culture factors have not been able to be optimally implemented as they should. Criminalization of abandonment of Coal Mining Business License by corporations is very important (urgent), where administrative sanctions provided by the Government related to corporations that do not carry out the obligation to submit RKAB are...